A Deep Dive into Sustainable Garlic Production in Indonesia: A Multidimensional Scaling Approach - Puspitasari; Nurmalina, Rita; Hariyadi; Agustian, Adang (Universitas Muhammadiyah Yogyakarta, 2025)
Efforts to overcome the dependence on garlic imports in Indonesia by raising its production have not yet been achieved. Various challenges have emerged, threatening the sustainability of garlic production and escalating the annual volume of imports. It is imperative to evaluate the initiatives undertaken to ensure the sustainability of garlic production. To address the issue, this study assessed the sustainability of garlic production and identified the leverage factors affecting it. This study employed the Multidimensional Scaling (MDS) method by examining indicators across five dimensions. Sustainability scores were derived through expert judgment via interviews and Focus Group Discussions with 74 participants. This research discovered moderate sustainability levels, with the economic dimension exhibiting the lowest index. Consequently, garlic farming faced considerable challenges and obstacles stemming from economic factors, potentially disrupting the sustainability of its production. Based on the identified leverage variables, this study recommends five specific interventions to improve garlic production sustainability: constructing water reservoirs and developing irrigation infrastructure, implement a minimum purchasing price and restricting import quotas during peak harvest, enhancing the selling value of local garlic by promoting its superiority, making significant efforts to develop research aimed at producing high-quality seeds in mass quantities, and establishing a robust marketing institution at the farmer level.